Basic infection control for health care providers - Kennamer, Mike (Thomson/Delmar Learning, 2006)
Basic Infection Control for Health Care Providers, Second Edition, is a clear and concise guide to preventing occupational exposure hazards and communicable and infectious diseases. This book includes coverage on how to safely protect oneself from infectious agents and what do in case of infectious exposure. Discussions of the disease process and legal issues surrounding exposure and infectious diseases provide context for the material. The blend of fundamental infection control content and reference resources makes this tool perfect for use in an instructional setting or as a reference for practicing health care providers.